Pengaruh Kualitas Pelayanan dan Kelengkapan Produk terhadap Keputusan Pembelian di Apotek Winola Medika Maumere - Nelfiana Nggagho; Antonius Philipus Kurniawan; Yosef Tonce (Jurnal CUAN Universitas Nusa Nipa Maumere, 2024)
The background of this research is how much effect service quality and product completeness have on purchasing decisions at Winola Medika Maumere Pharmacy. This research aimed to (1) determine the description of service quality and product completeness on purchasing decisions at Winola Medika Maumere Pharmacy, (2) Know the effect of service quality on purchasing decisions at the Winola Medika Maumere Pharmacy, (3) Know the effect of product completeness on purchasing decisions at the Winola Medika Maumere Pharmacy, (4) Know the simultaneous effect of service quality and product completeness on purchasing decisions at the Winola Medika Maumere Pharmacy. The population in this research were consumers who bought products at the Winola Medika Maumere Pharmacy using the Lemeshow formula. The sample in this research amounted to 100 respondents. Data was collected through questionnaires and analyzed through descriptive statistical methods and multiple linear regression statistics. Hypothesis testing was done through a partial tests "t-test" and simultaneous tests "f-test". The results of descriptive statistical analysis showed that the respondent's perceptions of the purchasing decision variable of 62.35% were categorized as quite good and then the respondents’ perceptions for the service quality variable were 70.48% in the good category, the respondents’ perceptions of the product completeness variable of 64.65% were categorized as quite good. The results of the "t-test" showed that the service quality variable (X1) had a significant effect on the purchasing decision variable (Y) and the product completeness variable (X2) had a significant effect on the purchasing decision variable (Y). The results of the simultaneous test "f-test" showed that the variables of service quality (X1) and product completeness (X2) had a significant effect on purchasing decisions (Y). In addition, the results of the determination analysis (R2) on the contribution of the service quality and product completeness variables to purchasing decisions at the Winola Medika Maumere Pharmacy is 18.3%, while 81.7% is influenced by other factors outside the research variables.